ANALISA WEBSITE MOODLE PT XYZ DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 - Emeraldi Destian Rasman (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
Quality is the features or products that meet customer needs and can meet customer satisfaction. Website is something that must be considered by the institution in this case the educational institution, because it is used by users who are in the institution. To find out the quality of the website it is necessary to measure the quality of the academic website owned by the PT XYZ. The instrument used in this study is Webqual 4.0 (Barnes & Vidgen, 2001) which consists of 4 variables, namely Usability, Information Quality, Service Interaction, User Satisfaction, and has 14 indicators. The analysis technique used is Multiple Linear Regression which will provide an overview of the relationship between website quality and user satisfaction. This research was conducted by distributing questionnaires to 68 students of the PT XYZ. The validity, reliability, and data analysis tests were performed using the SPSS 16 application. The results of the analysis in the partial test showed that the quality of usability and service interaction had an influence on user satisfaction (User Satisfaction). While the quality of information (Information Quality) does not have an influence on user satisfaction (User Satisfaction) because the test results show a negative effect and do not meet the requirements of significance test and t test. In the F test results, it shows that Usability, Information Quality and Service Interaction together have a significant effect on user satisfaction (User Satisfaction). And the results of testing all independent variables Usability, Information Quality, and Service Interaction show the level of user satisfaction or User Satisfaction of 41.9%. Where all independent variables affect user satisfaction by 41.9%.